Realization of vocational high school curriculum based on work culture - Ahyanuardi Ahyanuardi; Sri Rahmadhani; Lili Suryati; Zuryana Zuryana (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
This research aims to find out the implementation of work attitudes based on the business world, the industry, and the world of work in the curriculum used by vocational high schools, where the work culture is a work attitude that prospective workers must own in entering the workforce. The realization of this work culture is seen from several indicators such as the application of work culture needed in schools, the existence of Links and Matches with the needs of the world of work, interpersonal skills owned by students, and intrapersonal abilities possessed by students who are realized in the 5R work culture (Concise, Neat, Resik, Care and Rajin) that apply to the school curriculum. The method used in this research is the Mixed Methode method, combining quantitative research and qualitative research. The study was conducted using instrument questionnaires and structured and open interviews involving respondents from educational institutions and the world of work under the auspices of the Indonesian Electrical and Mechanical Contractors Association. The data analysis technique used is the Milles and Huberman model Likert scale by looking at the percentage generated on the indicator of the competence of the world of work in the good category of 63.73%. But this must remain a thing that needs to be considered and maintained by vocational high schools to produce graduates of good character and a good working culture.